Preliminary results on the effect of planting system on cost of establishment and soilage production with elephant grass (pennisetum purpureum) - Carvalho, Margarida M. de; Mozzer, Otto Luiz (Pesquisa Agropecuaria Brasileira, 2014)
Studies were made on small plots to determine the most efficient system of planting Elephant grass (Pennisetum purpureum). The usual method, of hand placing two inclined cuttings per hill leaving 1/3 of their lengths exposed, was compared with three other methods: A) two cuttings laid in the furrow and covered; B) the entire stalk including the leaves laid in a furrow and covered; C) the entire stalk the leaves laid in a furrow and covered. Results obtained from experiments in two different soil types permitted the following conclusions: 1. The planting systems that completely covered the canes were the most efficient. They produced the most sprouting specially when moisture conditions after planting were less than ideal. 2. Planting systems utilizing the complete stalk produced more forage than those using cuttings. However this difference was less after the first cutting. 3. Costs for preparing planting material and planting were less when the entire stalk with the leaves was used. This method required 13 man days per hectare. 4. Planting the entire stalk with or without the leaves resulted in equal yields. However, the removal of the leaves cost an additional 7 man days per hectare. 5. When the planting material is short or it is impossible to make furrows the use of cuttings should be given preference.